N13 Clinical service delivery implications of the Covid-19 pandemic on people with inflammatory bowel disease: a qualitative study. (21st January 2022) - Kemp, K; Avery, P; Bryant, R; Cross, A; Danter, K; Kneebone, A; Morris, D; Walker, A; Whitley, L; Dibley, L
Abstract: Background: As part of a qualitative study exploring the experiences of IBD patients during three UK lockdowns, we identified specific clinical service implications of the pandemic on IBD care. Methods: Participants aged 18 years+ with a confirmed diagnosis of Crohn's disease, Ulcerative Colitis or IBD-Unclassified, who had shielded or not during any lockdown period were recruited from Crohn's and Colitis UK. Semi-structured online or phone interviews (captured February-May 2021) were audio-recorded, transcribed professionally, and analysed using thematic analysis. Results: Forty-three people took part; median age 38 years (19–63 years); 27 (62.7%) females; diagnosed with Crohn's Colitis (n=2), Crohn's disease (n=21), Ulcerative colitis (n=18) and IBD-Unclassified (n=2). Median disease duration 13 years (0.6–36 years). Four clinically focussed themes emerged: The Risk of Attending Hospital ; Missing Routine Monitoring ; Accessing Care as Needed and Remote Access and The Future . The Risk of Attending Hospital: Against the prevailing media messages to avoid going to hospital, staying at home to avoid burdening the healthcare system and the rising numbers of Covid patients in hospitals, participants felt anxious about the dilemma of needing treatment for their IBD but putting themselves at risk to receive it. Missing Routine Monitoring: Routine appointments and monitoring, which participants relied on for 'keeping on top of' their condition, stopped for some. Many could not access their IBD team or GP services at all, so routine blood tests for therapeutic levels were missed; in some cases, disease activity increased. Accessing Care as Needed: Many were able to get clinical help as needed, even if the method of contact, and source of help, was different to usual. For others, the pandemic had caused considerable delay in getting diagnosed, and they felt overwhelmed and unsupported. Most understood the disruption to services due to staff redeployment, but some coped with the changes better than others. Remote Access and The Future: the shifting focus away from face to face and towards remote appointments received mixed opinions. Many were happy with remote (phone, email) contact during the pandemic, out of necessity, but there were concerns from others that this would become normal in the future. It was suggested that first appointments should always be face to face. Conclusion: Maintenance of IBD services in some form is essential throughout crisis periods; newly diagnosed patients needed additional support; dependence on IBD services could be reduced in the future through use of treatment/self-management plans. Mode of appointment needs to suit the patient.